Families - Beyond the Nuclear Ideal - Cutas, Daniela; Chan, Sarah (Science Ethics and Society, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book examines, through a multi-disciplinary lens, the possibilities offered by relationships and family forms that challenge the nuclear family ideal, and some of the arguments that recommend or disqualify these as legitimate units in our societies.That children should be conceived naturally, born to and raised by their two young, heterosexual, married to each other, genetic parents; that this relationship between parents is also the ideal relationship between romantic or sexual partners; and that romance and sexual intimacy ought to be at the core of our closest personal relationships - all these elements converge towards the ideal of the nuclear family. The authors consider a range of relationship and family structures that depart from this ideal: polyamory and polygamy, single and polyparenting, parenting by gay and lesbian couples, as well as families created through assisted human reproduction.